2016
DOI: 10.1007/s00404-016-4235-2
|View full text |Cite|
|
Sign up to set email alerts
|

Orally administered multispecies probiotic formulations to prevent uro-genital infections: a randomized placebo-controlled pilot study

Abstract: Both probiotic formulations F_1 and F_2, chosen because of their anti-microbial activity against pathogens responsible for vaginal dysbiosis and infections, led to vaginal detection and enhancement of the amount of species of formulates when orally administered. This work provides the basis for further clinical investigations of the F_1 and F_2 capacity to prevent or treat uro-genital infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
0
18
1
1
Order By: Relevance
“…Although oral probiotics can prevent and/or decrease frequency or severity of diseases outside of the gastrointestinal tract (i.e., an indirect effect) (Alberda et al, 2007; Lappin et al, 2009; Di Nardo et al, 2014; Esposito et al, 2014; Lee et al, 2015; Zuccotti et al, 2015; Fuchs-Tarlovsky et al, 2016; Gruner et al, 2016; Vieira et al, 2016; Zamani et al, 2016), few studies have directly evaluated the appearance of orally administered probiotic species or changes in host microbial communities at distant sites (De Alberti et al, 2015; Mastromarino et al, 2015; Treven et al, 2015). A recent study in pre-menopausal women demonstrated an increase in orally administered probiotic species in vaginal swabs using qPCR analysis, setting the stage for use of oral probiotics to prevent or treat urogenital infections (Mezzasalma et al, 2017). A combination of bovine lactoferrin and two probiotics administered to healthy women led to detection of the probiotic species in vaginal swabs, important pilot data for future studies of bacterial vaginosis (De Alberti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although oral probiotics can prevent and/or decrease frequency or severity of diseases outside of the gastrointestinal tract (i.e., an indirect effect) (Alberda et al, 2007; Lappin et al, 2009; Di Nardo et al, 2014; Esposito et al, 2014; Lee et al, 2015; Zuccotti et al, 2015; Fuchs-Tarlovsky et al, 2016; Gruner et al, 2016; Vieira et al, 2016; Zamani et al, 2016), few studies have directly evaluated the appearance of orally administered probiotic species or changes in host microbial communities at distant sites (De Alberti et al, 2015; Mastromarino et al, 2015; Treven et al, 2015). A recent study in pre-menopausal women demonstrated an increase in orally administered probiotic species in vaginal swabs using qPCR analysis, setting the stage for use of oral probiotics to prevent or treat urogenital infections (Mezzasalma et al, 2017). A combination of bovine lactoferrin and two probiotics administered to healthy women led to detection of the probiotic species in vaginal swabs, important pilot data for future studies of bacterial vaginosis (De Alberti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we have demonstrated that our oral food supplement Intimique Femme is effective in colonizing the vaginal epithelium and that both the single strains and their combination can inhibit a wide panel of harmful pathogens, responsible for several vaginal infections [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the strains Lactobacillus rhamnosus HS111 and Lactobacillus acidophillus HS101 were also probiotic species effective in the treatment of candidiasis of complete denture wearers [ 15 ]. Not only in the dental area, but also in gynecology, there is interest in the subject [ 22 24 ] since the uncontrolled growth of Candida species is also responsible for gynecological infections. However, studies employing the pathogenic Lactobacillus species in the treatment of Candida infections are scarce [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%